Cuando solo nos queda enseñar las cartas: sesgos androcéntricos en el análisis de la vida de Trota de Ruggiero. - González Gutiérrez, Patricia (Nomadías, 2018)
Our way of doing science and history is full of cultural biases, among which the androcentric bias, so present in our society, stands out. Sometimes, these ways of writing go unnoticed, but they are especially visible when dealing with the figure of historical women and, even more so, when we know little about their lives. Thus, the figure of the medical Trota de Ruggiero, is especially interesting to analyze how we conceive the history of women in science.